The Historical Jesus : Five Views - Beilby, James K. and Eddy, Paul R.; Beilby, James K; Eddy, Paul R (Downers Grove, Ill. : IVP Academic, 2009)
Five scholars offer their perspective on the quest for the historical Jesus and respond to the views of each other
The scholarly quest for the historical Jesus has a distinguished pedigree in modern Western religious and historical scholarship, with names such as Strauss, Schweitzer and Bultmann highlighting the story. Since the early 1990s, when the Jesus quest was reawakened for a third run, numerous significant books have emerged. And the public's attention has been regularly arrested by media coverage, with the Jesus Seminar or the James ossuary headlining the marquee. The Historical Jesus: Five Views provides a venue for readers to sit in on a virtual seminar on the historical Jesus. Beginning with a scene-setting historical introduction by the editors, prominent figures in the Jesus quest set forth their views and respond to their fellow scholars. On the one end Robert M. Price lucidly maintains that the probability of Jesus' existence has reached the "vanishing point," and on the other Darrell Bock ably argues that while critical method yields only a "gist" of Jesus, it takes us in the direction of the Gospel portraits. In between there are numerous avenues to explore, questions to be asked and "assured results" to be weighed. And John Dominic Crossan, Luke Timothy Johnson and James D. G. Dunn probe these issues with formidable knowledge and honed insight, filling out a further range of options. The Historical Jesus: Five Views offers a unique entry into the Jesus quest. For both the classroom and personal study, this is a book that fascinates, probes and engages
Jesus at the vanishing point / Robert M. Price -- Jesus and the challenge of collaborative eschatology / John Dominic Crossan -- Learning the human Jesus : historical criticism and literary criticism / Luke Timothy Johnson -- Remembering Jesus : how the quest of the historical Jesus lost its way / James D.G. Dunn -- The historical Jesus : an evangelical view / Darrell L. Bock
Includes bibliographical references and indexes
Keywords: Jesus Christ -- Historicity -- History of doctrines -- 21st century; Historical Study - Jesus; Collaborative Eschatology; Study - Human Jesus - Works